Scales of tectonic processes controlling fluid flow systems on the Svyatogor Ridge, Fram Strait - Waghorn, Kate Alyse (Geochemistry, Geophysics, Geosystems, 2019)
The Svyatogor Ridge, located in the Fram strait, is a site hosting a fluid flow system. The Svyatogor Ridge is part of the inside corner high at the Knipovich Ridge-Molloy Transform fault intersection. The Knipovich Ridge is an ultra-slow, melt-poor spreading ridge with approximately 8 mm/yr spreading rate. At this northernmost segment of the Knipovich Ridge, spreading is predominantly accommodated by crustal scale detachment faults. While fluid flow systems are not atypical on mid-ocean ridge flanks, the geothermal gradients are generally too warm and sediment cover too underdeveloped for generation and formation of gas hydrates, despite methane release from hydrothermal vent systems being well documented. In this study area, the convergence of a well developed sedimentary cover atop partially serpentinized ultra-mafic mantle material and a comparatively cool geothermal gradient entails a gas hydrate system in an unusual location. This thesis characterises a potential abiotic methane hydrate accumulation site in terms of structure, sedimentology, evolution and fluid flow systems. We find a link between crustal faulting in serpentinized mantle material and gas hydrate/free gas accumulations leading to the conclusion that abiotic methane is likely contributing to the gas hydrate system here. The stress regime has been an important factor on the Svyatogor Ridge for controlling fluid flow through geological time and into the future. High-resolution 3D P-Cable seismic data was integral for identifying fault and fracture networks, which drive fluid migration as normal extensional faulting becomes sub-optimally positioned for fluid migration.